The Impact and Mechanism of Trade Rules on Digital Services Trade Competitiveness: An Empirical Analysis Based on Regional Trade Agreements - Cheng, Dawei (Journal of Global Economy, Business and Finance, 2025)
Drawing upon data from regional trade agreements involving 131 countries and their partner nations between 2005 and 2023, this empirical study examines how the breadth and depth of digital trade rules within regional trade agreements influence a country’s competitiveness in digital services trade. Employing a two-way fixed effects model, the study uses the digital services trade competitiveness index as the dependent variable, with the breadth and depth of digital trade rules as core explanatory variables, while controlling for factors such as economic development levels and national characteristics. Results indicate that both the breadth and depth of digital trade rules significantly enhance digital services trade competitiveness, a conclusion validated through robustness tests and endogeneity treatment. Mechanism analysis reveals that digital trade rules enhance competitiveness through two pathways: reducing institutional distance and lowering data flow costs. Based on these findings, China should actively participate in and lead the development of digital trade rules, promote the implementation of high-standard provisions, and narrow institutional gaps with partner countries through regional trade agreements to enhance its international competitiveness in digital services trade.